Preparation method of PBAT copolymerization modified material
Through the copolymerization of raw materials such as terephthalic acid, adipic acid, and furandicaric acid, PBAT copolymerization modified materials were prepared, which solved the problems of insufficient toughness of PLA materials and high cost of PBAT materials, and achieved improvement of material performance and reduction of cost. , suitable for a variety of applications.
Patent Information
- Application Number
- CN202411773146.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-01-14
AI Technical Summary
Polylactic acid (PLA) materials have poor toughness, which limits its application range. Although polyadipate-butadiene terephthalate (PBAT) materials have good flexibility and impact resistance, they have high production costs. Poor thermodynamic performance limits its application field.
Copolymerization is carried out using raw materials such as terephthalic acid, adipic acid, furandicarboxylic acid, lactic acid, 1,4-butanediol and isosorbide. PBAT copolymerization is prepared through specific process steps and catalyst addition, and PBAT copolymerization is improved. Tensile strength and toughness of the material.
The obtained PBAT copolymerized modified materials have high tensile strength and toughness, better performance than a single material, suitable for a variety of applications, while reducing production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biodegradable materials, and in particular relates to a method for preparing a PBAT copolymer modified material. Background Art
[0002] With the increasing global concern about environmental issues, reducing plastic pollution has become a common goal of governments and people around the world. Degradable plastics can be decomposed into harmless substances under appropriate conditions and have lower environmental impact than traditional plastics. Many countries and regions have introduced relevant policies and regulations to restrict or prohibit the use of traditional plastics and encourage the research and development and application of degradable plastics. With the continuous advancement of science and technology, the performance and stability of degradable plastics are constantly improving. The research and development and improvement of new degradable plastic materials will make them more suitable for various fields and meet the requirements of different industries for material performance. For example, the research on new materials such as bio-based degradable plastics and sodium alginate will bring more possibilities to the industry. Consumers' demand for environmentally friendly products is gradually increasing, and more and more people are beginning to pay attention to the problem of plastic pollution and choose to use degradable plastic products. At the same time, some companies have also realized that the use of degradable plastics can enhance their image and brand value. Degradable plastics play an important role in the circular economy model. Through recycling and reuse, degradable plastics can become a sustainable resource, reduce dependence on raw materials, and reduce waste emissions. In general, as an environmentally friendly material, degradable plastics have great development prospects.
[0003] Polylactic acid (PLA) is a biodegradable polymer material derived from renewable resources. It has good mechanical strength and modulus, biocompatibility, and optical properties, and is widely used in medicine, packaging, agriculture, and other fields. However, PLA has poor toughness, and its elongation at break and notched impact strength are low, which limits the application of PLA in toughness requirements.
[0004] Polybutylene adipate-terephthalate (PBAT) is currently the most important petroleum-based biodegradable plastic. It has good flexibility, impact resistance, thermal stability, and is soft and transparent. Its mechanical properties such as stretching and elongation are similar to those of low-density polyethylene (LDPE). However, compared with traditional plastics, the high proportion of amorphous regions and low crystallinity in PBAT affect the strength of the material. At the same time, it has disadvantages such as high production costs and poor thermodynamic properties, which limits its application areas. Summary of the invention
[0005] In order to overcome the above shortcomings, the present invention provides a method for preparing a PBAT copolymer modified material.
[0006] A method for preparing a PBAT copolymer modified material comprises the following steps: (1) Weigh 70-90 parts of terephthalic acid, 40-50 parts of adipic acid, 30-50 parts of furandicarboxylic acid, and 15-40 parts of lactic acid in proportion, add them into a reaction vessel a, and stir evenly for 0-24 hours; (2) Weigh an appropriate amount of 90-120 parts of 1,4-butanediol and 12-25 parts of isosorbide into reaction vessel a and continue stirring for 0-24 hours; (3) adding catalysts such as zinc acetate, tetrabutyl titanate and triphenyl phosphate; (4) The reaction vessel a is evacuated, filled with nitrogen or argon, and replaced with inert gas three times; (5) The reaction vessel a is heated to 80-100°C in the first stage of the reaction, and stirred for 1-2 hours at the temperature maintained at that temperature. In the second stage of the reaction, the temperature is further raised to 140-160°C, and stirred for 1-2 hours at the temperature maintained at that temperature. At this time, the catalyst antimony trioxide is added, and stirring is continued for 1-2 hours at this temperature.
[0007] (6) Turn on the vacuum pump and maintain the vacuum pressure at 0~50Pa.
[0008] (7) Continue to raise the temperature to 210-240°C and continue the reaction for 2-10 hours.
[0009] (8) Fill with nitrogen, turn off the heating, and cool down to obtain the PBAT copolymer modified material.
[0010] Furthermore, the zinc acetate is 0.1‰ to 10‰ of the total mass of the terephthalic acid, adipic acid, furandicarboxylic acid, lactic acid, 1,4-butanediol and isosorbide; The tetrabutyl titanate is 0.1‰ to 10‰ of the total mass of the terephthalic acid, adipic acid, furandicarboxylic acid, lactic acid, 1,4-butanediol and isosorbide; The triphenyl phosphate is 0.1‰ to 10‰ of the total mass of the terephthalic acid, adipic acid, furandicarboxylic acid, lactic acid, 1,4-butanediol and isosorbide.
[0011] Furthermore, the mass of antimony trioxide is 0.1‰~10‰ of the total mass of all acids and alcohols.
[0012] The present invention starts from improving material performance and reducing costs, adopts terephthalic acid, adipic acid, 1,4-butanediol, furandicarboxylic acid, isosorbide, lactic acid and the like as raw materials, and carries out copolymerization synthesis to obtain a new type of degradable material, and the obtained material has the characteristics of high tensile strength and good toughness. DETAILED DESCRIPTION
[0013] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example
[0014] (1) Weigh 83 g of terephthalic acid, 43.8 g of adipic acid, 31.2 g of furandicarboxylic acid, and 27 g of lactic acid, add them into a reaction vessel a, and stir evenly for 0.5 h.
[0015] (2) Weigh 108 g of 1,4-butanediol and 14.6 g of isosorbide, add them into reaction vessel a, and continue stirring for 0.5 h.
[0016] (3) Add 0.15 g of zinc acetate, 0.15 g of tetrabutyl titanate and 0.15 g of triphenyl phosphate as catalysts.
[0017] (4) The reaction vessel a was evacuated and replaced with nitrogen three times.
[0018] (5) The reaction vessel a is heated to 100°C for the first stage reaction and stirred for 1 hour at this temperature. The second stage reaction is further heated to 160°C and stirred for 1 hour at this temperature. At this time, 0.1 g of antimony trioxide catalyst is added. Stirring is continued at this temperature for 2 hours.
[0019] (6) Turn on the vacuum pump and keep the vacuum pressure below 50Pa.
[0020] (7) Continue to raise the temperature to 220°C and continue the reaction for 6 hours.
[0021] (8) Fill with nitrogen, turn off the heating, and cool down to obtain the modified PBAT material.
[0022] The copolymer modified material is placed into a flat vulcanizer and processed into a film according to the following method for performance testing.
[0023] (1) Before lamination, a layer of polyimide film is placed on both the upper and lower plates to prevent the modified material from bonding to the upper and lower plates after heating and pressing.
[0024] (2) Take 15g of PBAT copolymer modified material and place it in the middle of the upper and lower feeding plates.
[0025] (3) Set the temperature of the hot pressing plate to 170°C.
[0026] (4) Set the vulcanization time to 300s and the exhaust times to 3 times.
[0027] (5) Set the pressure of the first stage (pre-pressure 3 MPa) and the second stage (boosting pressure 12 MPa).
[0028] (6) When the temperature is reached, place the plate with the raw materials in the middle of the heated template, press the mold closing key to raise and close the template to start the molding process.
[0029] (7) After molding for 300 seconds and cooling for 360 seconds, the mold is opened and the biodegradable film is taken out.
[0030] The obtained film material was tested for performance, and the glass transition temperature was -11.2℃, the melting point was 138℃, the elastic modulus was 126MPa, and the tensile strength was 26MPa. The CO2 barrier was 1.1barrer, the O2 barrier was 0.22barrer, and the water vapor barrier was 1.8×10-13g.cm / cm2.s.Pa. Example
[0031] (1) Weigh 83 g of terephthalic acid, 43.8 g of adipic acid, 31.2 g of furandicarboxylic acid, and 27 g of lactic acid, add them into a reaction vessel a, and stir evenly for 0.5 h.
[0032] (2) Weigh 108 g of 1,4-butanediol and 22 g of isosorbide, add them into reaction vessel a, and continue stirring for 0.5 h.
[0033] (3) Add 0.15 g of zinc acetate, 0.15 g of tetrabutyl titanate and 0.1 g of triphenyl phosphate as catalysts.
[0034] (4) The reaction vessel a was evacuated and replaced with nitrogen three times.
[0035] (5) The reaction vessel a is heated to 100°C for the first stage reaction and stirred for 1 hour at this temperature. The second stage reaction is further heated to 160°C and stirred for 1 hour at this temperature. At this time, 0.1 g of antimony trioxide catalyst is added. Stirring is continued at this temperature for 2 hours.
[0036] (6) Turn on the vacuum pump and keep the vacuum pressure below 50 Pa.
[0037] (7) Continue to raise the temperature to 230°C and continue the reaction for 6 hours.
[0038] Fill with nitrogen, turn off the heating, and cool down to obtain the modified PBAT material.
[0039] The film preparation method is the same as that in Example 1. The obtained film material is subjected to performance testing, and the glass transition temperature is -8.1°C, the melting point is 140°C, the elastic modulus is 135MPa, and the tensile strength is 29MPa. The CO2 barrier is 0.7barrer; the O2 barrier is 0.16barrer, and the water vapor barrier is 1.62×10-13g.cm / cm2.s.Pa. Example
[0040] (1) Weigh 83 g of terephthalic acid, 43.8 g of adipic acid, 31.2 g of furandicarboxylic acid, and 18 g of lactic acid, add them into a reaction vessel a, and stir evenly for 0.5 h.
[0041] (2) Weigh 108 g of 1,4-butanediol and 22 g of isosorbide, add them into reaction vessel a, and continue stirring for 0.5 h.
[0042] (3) Add 0.15 g of zinc acetate, 0.15 g of tetrabutyl titanate and 0.1 g of triphenyl phosphate as catalysts.
[0043] (4) The reaction vessel a was evacuated and replaced with nitrogen three times.
[0044] (5) The reaction vessel a is heated to 100°C for the first stage reaction and stirred for 1 hour at this temperature. The second stage reaction is further heated to 160°C and stirred for 1 hour at this temperature. At this time, 0.1 g of antimony trioxide catalyst is added. Stirring is continued at this temperature for 2 hours.
[0045] (6) Turn on the vacuum pump and keep the vacuum pressure below 50 Pa.
[0046] (7) Continue to raise the temperature to 230°C and continue the reaction for 6 hours.
[0047] Fill with nitrogen, turn off the heating, and cool down to obtain the modified PBAT material.
[0048] The film preparation method is the same as that in Example 1. The obtained film material is subjected to performance tests, and the glass transition temperature is -2.1°C, the melting point is 140°C, the elastic modulus is 135MPa, and the tensile strength is 38MPa. The CO2 barrier is 0.5barrer; the O2 barrier is 0.13barrer, and the water vapor barrier is 8.2×10-14g.cm / cm2.s.Pa. Example
[0049] (1) Weigh 83 g of terephthalic acid, 43.8 g of adipic acid, 31.2 g of furandicarboxylic acid, and 40 g of lactic acid, add them into a reaction vessel a, and stir evenly for 0.5 h.
[0050] (2) Weigh 108 g of 1,4-butanediol and 14.6 g of isosorbide, add them into reaction vessel a, and continue stirring for 0.5 h.
[0051] (3) Add 0.15 g of zinc acetate, 0.15 g of tetrabutyl titanate and 0.1 g of triphenyl phosphate as catalysts.
[0052] (4) The reaction vessel a was evacuated and replaced with nitrogen three times.
[0053] (5) The reaction vessel a is heated to 100°C for the first stage reaction and stirred for 1 hour at this temperature. The second stage reaction is further heated to 160°C and stirred for 1 hour at this temperature. At this time, 0.1 g of antimony trioxide catalyst is added. Stirring is continued at this temperature for 2 hours.
[0054] (6) Turn on the vacuum pump and keep the vacuum pressure below 50 Pa.
[0055] (7) Continue to raise the temperature to 230°C and continue the reaction for 6 hours.
[0056] Fill with nitrogen, turn off the heating, and cool down to obtain the modified PBAT material.
[0057] The film preparation method is the same as that in Example 1. The obtained film material is subjected to performance testing, and the glass transition temperature is -8.6°C, the melting point is 137°C, the elastic modulus is 129MPa, and the tensile strength is 27MPa. The CO2 barrier is 0.7barrer; the O2 barrier is 0.2barrer, and the water vapor barrier is 1.7×10-13g.cm / cm2.s.Pa. Example
[0058] (1) Weigh 83 g of terephthalic acid, 43.8 g of adipic acid, 46.8 g of furandicarboxylic acid, and 27 g of lactic acid, add them into a reaction vessel a, and stir evenly for 0.5 h.
[0059] (2) Weigh 108 g of 1,4-butanediol and 14.6 g of isosorbide, add them into reaction vessel a, and continue stirring for 0.5 h.
[0060] (3) Add 0.15 g of zinc acetate, 0.15 g of tetrabutyl titanate and 0.1 g of triphenyl phosphate as catalysts.
[0061] (4) The reaction vessel a was evacuated and replaced with nitrogen three times.
[0062] (5) The reaction vessel a is heated to 100°C for the first stage reaction and stirred for 1 hour at this temperature. The second stage reaction is further heated to 160°C and stirred for 1 hour at this temperature. At this time, 0.1 g of antimony trioxide catalyst is added. Stirring is continued at this temperature for 2 hours.
[0063] (6) Turn on the vacuum pump and keep the vacuum pressure below 50 Pa.
[0064] (7) Continue to raise the temperature to 230°C and continue the reaction for 6 hours.
[0065] Fill with nitrogen, turn off the heating, and cool down to obtain the modified PBAT material.
[0066] The film preparation method is the same as that in Example 1. The obtained film material is subjected to performance testing, and the glass transition temperature is -5.2°C, the melting point is 130°C, the elastic modulus is 110MPa, and the tensile strength is 23MPa. The CO2 barrier is 1.3barrer; the O2 barrier is 0.25barrer, and the water vapor barrier is 2×10-13g.cm / cm2.s.Pa.
[0067] (1) Weigh 83 g of terephthalic acid and 43.8 g of adipic acid, add them into a reaction vessel a, and stir evenly for 0.5 h.
[0068] (2) Weigh 90 g of 1,4-butanediol and add it to reaction vessel a. Stir continuously for 0.5 h.
[0069] (3) Add 0.1 g of zinc acetate, 0.1 g of tetrabutyl titanate and 0.07 g of triphenyl phosphate as catalysts.
[0070] (4) The reaction vessel a was evacuated and replaced with nitrogen three times.
[0071] (5) The reaction vessel a is heated to 100°C for the first stage reaction and stirred for 1 hour at this temperature. The second stage reaction is further heated to 160°C and stirred for 1 hour at this temperature. At this time, 0.07 g of antimony trioxide catalyst is added. Stirring is continued at this temperature for 2 hours.
[0072] (6) Turn on the vacuum pump and keep the vacuum pressure below 50 Pa.
[0073] (7) Continue to raise the temperature to 230°C and continue the reaction for 6 hours.
[0074] Fill with nitrogen, turn off the heating, and cool down to obtain the PBAT material.
[0075] The film preparation method is the same as that in Example 1. The obtained film material is subjected to performance tests, and the glass transition temperature is -36°C, the melting point is 122°C, the elastic modulus is 96MPa, and the tensile strength is 20MPa. The CO2 barrier is 5.8barrer; the O2 barrier is 0.74barrer, and the water vapor barrier is 3.4×10-13g.cm / cm2.s.Pa.
[0076] (1) Weigh 83 g of terephthalic acid and 43.8 g of adipic acid, add them into a reaction vessel a, and stir evenly for 0.5 h.
[0077] (2) Weigh 90 g of 1,4-butanediol and add it to reaction vessel a. Stir continuously for 0.5 h.
[0078] (3) Add 0.15 g of zinc acetate, 0.15 g of tetrabutyl titanate and 0.1 g of triphenyl phosphate as catalysts.
[0079] (4) The reaction vessel a was evacuated and replaced with nitrogen three times.
[0080] (5) The reaction vessel a is heated to 100°C for the first stage reaction and stirred for 1 hour at this temperature. The second stage reaction is further heated to 160°C and stirred for 1 hour at this temperature. At this time, 0.1 g of antimony trioxide catalyst is added. Stirring is continued at this temperature for 2 hours.
[0081] (6) Turn on the vacuum pump and keep the vacuum pressure below 50 Pa.
[0082] (7) The temperature was continued to rise to 230°C and the reaction was continued for 6 hours.
[0083] Fill with nitrogen, turn off the heating, and cool down to obtain the PBAT material.
[0084] The film preparation method is the same as that in Example 1. The obtained film material is subjected to performance testing, and the glass transition temperature is -35°C, the melting point is 123°C, the elastic modulus is 96MPa, and the tensile strength is 21MPa. The CO2 barrier is 5.7 barrer; the O2 barrier is 0.76barrer, and the water vapor barrier is 3.2×10-13g.cm / cm2.s.Pa.
[0085] For specific comparison results, see the table below.
Claims
1. A method for preparing a PBAT copolymer modified material, comprising the following steps: (1) Weigh 70-90 parts of terephthalic acid, 40-50 parts of adipic acid, 30-50 parts of furandicarboxylic acid, and 15-40 parts of lactic acid in proportion, add them into a reaction vessel a, and stir evenly for 0-24 hours; (2) Weigh an appropriate amount of 90-120 parts of 1,4-butanediol and 12-25 parts of isosorbide into reaction vessel a and continue stirring for 0-24 hours; (3) adding catalysts such as zinc acetate, tetrabutyl titanate and triphenyl phosphate; (4) The reaction vessel a is evacuated, filled with nitrogen or argon, and replaced with inert gas three times; (5) The reaction vessel a is heated to 80-100°C in the first stage of the reaction, and stirred for 1-2 hours at the temperature maintained at that temperature. In the second stage of the reaction, the temperature is further raised to 140-160°C, and stirred for 1-2 hours at the temperature maintained at that temperature. At this time, the catalyst antimony trioxide is added, and stirring is continued for 1-2 hours at this temperature.
2. (6) Turn on the vacuum pump and maintain the vacuum pressure at 0~50Pa.
3. (7) Continue to raise the temperature to 210-240°C and continue the reaction for 2-10 hours.
4. (8) Fill with nitrogen, turn off the heating, and cool down to obtain the PBAT copolymer modified material.
5. The method for preparing a PBAT copolymer modified material according to claim 1, characterized in that: The zinc acetate is 0.1‰ to 10‰ of the total mass of the terephthalic acid, adipic acid, furandicarboxylic acid, lactic acid, 1,4-butanediol and isosorbide; The tetrabutyl titanate is 0.1‰ to 10‰ of the total mass of the terephthalic acid, adipic acid, furandicarboxylic acid, lactic acid, 1,4-butanediol and isosorbide; The triphenyl phosphate is 0.1‰ to 10‰ of the total mass of the terephthalic acid, adipic acid, furandicarboxylic acid, lactic acid, 1,4-butanediol and isosorbide.
6. The method for preparing a PBAT copolymer modified material according to claim 1, characterized in that: The mass of antimony trioxide is 0.1‰~10‰ of the total mass of all acids and alcohols.
Citation Information
Cited By
Preparation method of naphthyl polyester-polycarbonate-polyether glycol and method for synthesizing novel polyester by using naphthyl polyester-polycarbonate-polyether glycol
CN121226695A